PENGARUH 6-BENZILAMINOPURIN (BAP) TERHADAP PEMBENTUKAN LAPISAN PEMISAH (ZONA ABSISI) PADA TANGKAI KUNTUM BUNGA KACANG HIJAU, VIGNA RADIATA (L.) Wilczek VARITAS WALET - Kusdianti, Kusdianti; Wardini, Trimurti H (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2002)
The effect of 6-benzylaminopurine (BAP) on separation layer formation of mungbean Vigna radiata (L.) Wilczek var. walet was carried out. The objective was to know the effect of BAP on separation layer formation. The experiment was done by spraying the first inflorescent with 8 x 10-4 M BAP three days before and three days after the fifth flower was anthesis.Â Samples of flower pedicellus were taken three days before dan three days after fifth flower was bloom. Then they wereÂ fixed and processed for anatomical observation by preparing histological slides accoding to Oâ€™Brien and Horner (1981). The result show that in control plant, two days before the fifth flower started to anthesis, cells of the abscission zone started to be activated to form separation layer. It was initiated by cell division within the adaxial edge and progressing inward across the cortex to the vascular strands. Abscission layer was completed at the time or a day after the fifth flower was anthesis. No histological changes observed in with 8 x 10-4 M BAP treated plant. No abscission layer were recorded for the pedicels treated plant during the course of the experiment.